2010
DOI: 10.1111/j.1365-246x.2010.04704.x
|View full text |Cite
|
Sign up to set email alerts
|

Refined thresholds for non-linear ground motion and temporal changes of site response associated with medium-size earthquakes

Abstract: S U M M A R YWe systematically analyse non-linear effects and temporal changes of site response associated with medium-size earthquakes, using seismic data recorded by the Japanese Strong Motion Network KIK-Net. We apply a sliding-window spectral ratio technique to surface and borehole strong motion records at six sites, and stack results associated with different earthquakes that produce similar peak ground acceleration (PGA). In some cases we observe a weak coseismic drop in the peak frequency when the PGA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Previous studies have found clear evidences of soil nonlinearity after previous large earthquakes in Japan, including the 1995 M w 6.8 Kobe earthquake, 2000 M w 6.8 Western Tottori earthquake, 2003 M w 8.3 Tokachi-Oki earthquake, 2003 M w 7.0 Miyaki-Oki earthquake, and 2004 M w 6.6 Niigata earthquake (e.g., Pavlenko and Irikura 2002;Sawazaki et al, 2006;Rubinstein et al, 2007;Assimaki et al, 2008;Wu et al, 2009aWu et al, , 2010. The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found clear evidences of soil nonlinearity after previous large earthquakes in Japan, including the 1995 M w 6.8 Kobe earthquake, 2000 M w 6.8 Western Tottori earthquake, 2003 M w 8.3 Tokachi-Oki earthquake, 2003 M w 7.0 Miyaki-Oki earthquake, and 2004 M w 6.6 Niigata earthquake (e.g., Pavlenko and Irikura 2002;Sawazaki et al, 2006;Rubinstein et al, 2007;Assimaki et al, 2008;Wu et al, 2009aWu et al, , 2010. The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Beresnev & Wen 1996;Wu et al 2010;Bonilla et al 2011;Rubinstein 2011;Wu & Peng 2011;Régnier et al 2013). However, non-linear soil behaviour is defined and studied in soil mechanics in the shear stressstrain plane.…”
Section: Shear Stress-strain Loopsmentioning
confidence: 99%
“…Beresnev & Wen 1996;Wu et al 2010;Bonilla et al 2011;Rubinstein 2011;Wu & Peng 2011). We then study the maximum shear strain related to the shear modulus reduction and the damping increase through the curves presented in Fig.…”
Section: N F L U E N C E O F T H E B a S I N S T Ru C T U R E : L Amentioning
confidence: 99%
“…The reference value of resonance frequency before the Tohoku earthquake is obtained by averaging all the resonance frequencies measured from the spectral ratio traces with PGA < 100 Gal before the Tohoku main shock. Here we choose the threshold of 100 Gal to avoid the influences of significant nonlinear effects from moderate to large ground motions (Beresnev and Wen, 1996;Wu et al, 2010). Next, we estimate a rough recovery time by the following two steps: we first average the resonance frequencies measured from all the spectral ratios traces with PGA < 100 Gal in the last month of data (07/12/2011-08/12/2011), and then we find the time point when the resonance frequency recover to 95% of the average resonance frequency in the last month.…”
Section: General Observationsmentioning
confidence: 99%